Direct bioelectricity generation from sago hampas by Clostridium beijerinckii SR1 using microbial fuel cell - Jenol, Mohd Azwan; Ibrahim, Mohamad Faizal; Kamal Bahrin, Ezyana; Kim, Seung Wook; Abd. Aziz, Suraini (MDPI, 2019)
Microbial fuel cells offer a technology for simultaneous biomass degradation and biological electricity generation. Microbial fuel cells have the ability to utilize a wide range of biomass including carbohydrates, such as starch. Sago hampas is a starchy biomass that has 58% starch content. With this significant amount of starch content in the sago hampas, it has a high potential to be utilized as a carbon source for the bioelectricity generation using microbial fuel cells by Clostridium beijerinckii SR1. The maximum power density obtained from 20 g/L of sago hampas was 73.8 mW/cm2 with stable cell voltage output of 211.7 mV. The total substrate consumed was 95.1% with the respect of 10.7% coulombic efficiency. The results obtained were almost comparable to the sago hampas hydrolysate with the maximum power density 56.5 mW/cm2. These results demonstrate the feasibility of solid biomass to be utilized for the power generation in fuel cells as well as high substrate degradation efficiency. Thus, this approach provides a promising way to exploit sago hampas for bioenergy generation.